Modelling accuracy of a car steering mechanism with rack and pinion and McPherson suspension - Knapczyk, Józef; Kucybała, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
Modelling accuracy of a car steering mechanism with a rack and pinion and McPherson suspension is analyzed. Geometrical parameters of the model are described by using the coordinates of centers of spherical joints, directional unit vectors and axis points of revolute, cylindrical and prismatic joints. Modelling accuracy is assumed as the differences between the values of the wheel knuckle position and orientation coordinates obtained using a simulation model and the corresponding measured values. The sensitivity analysis of the parameters on the model accuracy is illustrated by two numerical examples.
Keywords: steering mechanism; suspension; model; accuracy